Beca 18 y su relación con la reducción de la pobreza monetaria en Loreto 2019 - Vela Yuri, Jorge (2022)
Poverty is a socioeconomic evil that unfortunately haunts us since ancient times, even in the 21st century, it continues to affect a large part of the world population, especially in underdeveloped countries. In Peru, as a developing country, is not alien to this problem, according to the INEI, poverty decreased by 28.4 percentage points between 2006 and 2016, and 2017 poverty increased by 375,000 people or 1 percentage point (INEI , 2018), however there are still thousands of Peruvians who are in poverty and have a low educational level to get out of poverty, especially in the Loreto region, which according to the INEI, is one of the worst regions and with the worst academic performance in the country. This study seeks to determine the relationship of the Beca 18 program in the reduction of monetary poverty in the Loreto region, during the 2019 period, and also to determine the socioeconomic factors that influence the probability of being a beneficiary of the Beca 18 program, this is It is carried out by means of a methodology of a non-experimental nature, of a quantitative type and of correlational design, specifically a logistic regression model and a Pearson correlation analysis are used, in a sample of 24,882 individuals from the Loreto region; In our results we corroborate the existence of a positive relationship between participating in the Beca 18 program and the decrease in monetary poverty in the Loreto region, in the same way we corroborate the negative relationship between years of education and poverty. On the other hand, we find that being poor has a positive marginal benefit in the probability of participating in the scholarship program 18, as well as belonging to the informal sector, and economic variables such as income, spending and working hours have an effect negative in the probability of participating in the Beca 18 program, this is because this program is designed to support low-income students.